COUNTRY GOVERNANCE AND FINANCIAL LEVERAGE WITH INSTITUTIONAL OWNERSHIP AS MODERATING VARIABLES - Sasikirono, Nugroho (Universitas Muhammadiyah Surakarta, 2022)
This study aims to determine the effect of country governance and the components of country governance (voice and accountability, political stability and absence of violence, government effectiveness, regulatory quality, law, and control of corruption) on financial leverage, as well as the moderating effect of institutional ownership on the influence of country governance and the components of country governance (voice and accountability, political stability and absence violence, government effectiveness, regulatory quality, law, and control of corruption) on financial leverage. This study uses a sampling method using purposive sampling. The analysis method is multiple linear regression and moderated regression analysis. The number of samples in this study was 1853 observations on manufacturing companies listed on the stock exchanges of Indonesia, Malaysia, Thailand, Singapore, and the Philippines. The results show that country governance, political stability and absence aof violence, government effectiveness, regulatory quality, law, and control of corruption have a significantly negative effect on financial leverage, while voice and accountability have a significant positive on financial leverage. Institutional ownership weakens the negative influence of country governance, political stability and absence of violence, government effectiveness, regulatory quality, law, and control of corruption on financial leverage, while institutional ownership strengthens the positive effect of voice and accountability on financial leverage. In addition, tangible assets, profitability, interest rates, and GDP growth also affect financial leverage.